2001
DOI: 10.1063/1.1336571
|View full text |Cite
|
Sign up to set email alerts
|

Structural study of supercritical water. III. Rotational dynamics

Abstract: The rotational dynamics of water in super-and subcritical conditions is investigated by measuring the spin-lattice relaxation time T 1 of heavy water (D 2 O). The experimentally determined T 1 is shown to be governed by the quadrupolar relaxation mechanism even in the supercritical conditions and to provide the second-order reorientational correlation time 2R of the O-D axis of a single water molecule. It is then found that while 2R decreases rapidly with the temperature on the liquid branch of the saturation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
65
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 53 publications
(95 reference statements)
12
65
0
Order By: Relevance
“…A progressive increase of the pressure (density) from 50 to 180 bar (from 0.05 to 0.1 gؒcm -3 ) shows the occurrence of dimers in the fluid. These findings are in agreement with previously reported results [10,[14][15][16]. In particular, we note that the density threshold from which dimers occur, at about 0.04-0.05 gؒcm -3 , is in qualitative agreement with other experimental [10] and theoretical work [14].…”
Section: T Tassaing Et Alsupporting
confidence: 83%
See 1 more Smart Citation
“…A progressive increase of the pressure (density) from 50 to 180 bar (from 0.05 to 0.1 gؒcm -3 ) shows the occurrence of dimers in the fluid. These findings are in agreement with previously reported results [10,[14][15][16]. In particular, we note that the density threshold from which dimers occur, at about 0.04-0.05 gؒcm -3 , is in qualitative agreement with other experimental [10] and theoretical work [14].…”
Section: T Tassaing Et Alsupporting
confidence: 83%
“…In particular, we note that the density threshold from which dimers occur, at about 0.04-0.05 gؒcm -3 , is in qualitative agreement with other experimental [10] and theoretical work [14]. In addition, such a density threshold is also seen from NMR data [16] and molecular dynamics results [15] on rotational relaxation time.…”
Section: T Tassaing Et Alsupporting
confidence: 77%
“…To a first approximation, D 2 O exhibits the same PVT properties as H 2 O (Fig. 6); an observation consistent with the electrostatic and density properties of D 2 O measured at the nearcritical and supercritical region (Okada et al, 1999;Matubayasi et al, 2001;Bazaev et al, 2003).…”
Section: Isotopic and Chemical Equilibriumsupporting
confidence: 79%
“…Moreover, we have revealed that this behavior is more pronounced in the case of the first-order Legendre reorientational dynamics, whereas in the case of the second-order Legendre reorientational dynamics and especially for HBfree molecules, the corresponding reorientational times are not significantly affected by the bulk density. The sensitivity of the second-order reorientational times on the local HB network has also been mentioned in previous studies, 56 where it was also discussed that the effect of the local HB network is stronger in the liquid state than at supercritical conditions. Therefore, we may say that the first-order Legendre reorientational times could be considered as a better probe to analyze the effect of the local HB network on the reorientational dynamics in SCW.…”
Section: -3mentioning
confidence: 85%